THE ROLE OF NON-GOVERNMENTAL ORGANIZATIONS IN THE HEALTH CARE SECTOR IN UZBEKISTAN - Samadova Takhmina Muhiddinovna (American Journals, 2024)
This article analyzes the role, activities and problems of non-governmental organizations in the field of healthcare in Uzbekistan. Non-governmental organizations perform important tasks in improving public health, providing social protection and promoting a healthy lifestyle. The article examines their activities, emerging problems and future opportunities. Aspects such as research, innovation and cooperation opportunities are important in the development of the healthcare system in Uzbekistan.
Keywords: Non-Governmental Organizations Health Social Protection Healthy Lifestyle Medical Care Innovation Activists Challenges Cooperation.